2017
DOI: 10.1007/s12161-017-0951-x
|View full text |Cite|
|
Sign up to set email alerts
|

Antimony Assessment in PET Bottles for Soft Drink

Abstract: The aim of this work was to develop a method for the determination of antimony (Sb) in polyethylene terephthalate (PET) bottles and to evaluate its migration into soft drink and simulant. In this context, a new procedure for PET sample preparation, using a high pressure asher (HPA), is presented for the determination of Sb by inductively coupled plasma optical emission spectrometry (ICP-OES). The concentration of Sb in PET bottles ranged between 272 and 650 mg kg −1 . The migration of Sb into soft drink after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Interestingly enough, Sb was only quantified in PET-bottled beverages, supporting the hypothesis of migration of the specific metal from PET packaging to the beverage. The presence of Sb in PET-bottled drinks could be attributed to its usage as a catalyst during the production of PET, mostly in the Sb trioxide form [48,49]. Xu et al [50] examined the leaching and bioavailability of Sb in PET-bottled beverages across six categories (carbonated, fruit juices, tea, sports, protein, and coffee beverages).…”
Section: Elementsmentioning
confidence: 99%
“…Interestingly enough, Sb was only quantified in PET-bottled beverages, supporting the hypothesis of migration of the specific metal from PET packaging to the beverage. The presence of Sb in PET-bottled drinks could be attributed to its usage as a catalyst during the production of PET, mostly in the Sb trioxide form [48,49]. Xu et al [50] examined the leaching and bioavailability of Sb in PET-bottled beverages across six categories (carbonated, fruit juices, tea, sports, protein, and coffee beverages).…”
Section: Elementsmentioning
confidence: 99%
“…This characteristic raises concerns regarding the potential adverse effects of Sb species leached from PET bottles into water and beverages, necessitating a thorough evaluation of this phenomenon. However, the current literature predominantly focuses on the total migrated amount of Sb [ 12 , 13 , 15 , 16 , 17 ], with a very poor number of works focusing on its speciation [ 18 , 19 ], thus leaving the recognition of different Sb species as a significant knowledge gap. Moreover, the diverse PET production technologies lead to an extreme variability in the total amount of Sb present in the polymer and, importantly, Sb speciation (likely due to partial oxidation of Sb(III) during manufacturing) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, one can find reports about the release of elements from various container materials such as polyethylene (PET), glass, aluminum, or steel into beverages such as mineral water, juice, or soft drinks [8][9][10]. It was reported that some water additives such as citric acid can affect both the amount and the species in which certain elements are leached from bottle material [11][12][13][14][15]. In previous work, authors assessed the presence of toxic inorganic As, Cr, and Sb species in mineral water samples proving that those inorganic ionic species were present in that type of water [9,16].…”
Section: Introductionmentioning
confidence: 99%